The Effects of Class Schedules on the Focus and Punctuality of Senior High School Students - Marinell Moral; Leila Anne Tabien; France Mariella Napoles; Jane Cyrile Nunez; Cyruz Benn Guevara (Papanda Publisher, 2023)
This study aimed to investigate the effects of class schedules on the focus and punctuality of senior high school students, particularly the Grades 11 and 12, in Nazareth School of National University and compare its effects on the two different grade levels who start their face-to-face classes at different times. With the time their classes are scheduled, students may experience its effects on their ability to focus and be punctual in their classes. This study used a quantitative research design employing a descriptive-comparative approach as it enables understating the effects of different class schedules on the focus and punctuality of senior high school students and compares two different class schedules, namely the morning classes and afternoon classes. The study was conducted using a questionnaire with twenty-nine (29) items that aims to assess the focus and punctuality of senior high school students in their scheduled face-to-face classes. The study had hundred sixty-six (166) participants using a stratified sampling technique, particularly Grade 11 students who attend morning scheduled classes and Grade 12 who attend afternoon scheduled classes. The findings of the study showed that students from morning and afternoon scheduled classes may exhibit similar levels of focus and punctuality while there is no sufficient evidence to reject the null hypothesis of the study stating that there is no difference between morning and afternoon classes in terms of the focus of the students.